Catalogue of books printed before 1801 in the legal historical section of the Biblioteca di Scienze Sociali dell'Università degli Studi di Firenze II.1601-1700 - Osler, Douglas J. (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2014)
The present catalogue is the second of three volumes which record the books printed before 1801 currently held by the legal historical section of the Biblioteca di Scienze Sociali of the Università degli Studi di Firenze. This volume encompasses 2,424 editions published between 1601 and 1700. The present Florence library is the successor to that of the Facoltà di Giurisprudenza, the nucleus of which is the historic collection of the Collegio degli Avvocati di Firenze acquired in 1924. Supplemented by further important acquisitions, including the library of the Corte d'Appello, the collection has come to be numbered among the foremost in its field in Italy. The 17th century volume reflects primarily the Jurisprudence of the Baroque, the vast production of the jurists of Spain and Italy, but is by no means lacking in editions of the foremost jurists of contemporary Northern Europe.